Análise de Protocolos de Roteamento em MANETs como Apoio a Pervasividade em Ambientes Ubíquos - Schmidt, Ricardo de Oliveira (2007)
The scenarios of Ubiquitous Computing are becoming reality in the last years. The evolution in the technologies of wireless networks is making possible the existence of these ubiquitous scenarios. Mobile ad hoc networks (MANETs) are one of the main evolutions in networks area. These networks make possible the creation of communication structures in environments, until the moment, considered impossible. This way, the objective of this work was to evaluate two MANETs routing protocols in a scenario with high mobility: DYMO and OLSR. It also presents the methodology proposed to make the simulations used in the performance evaluation of the protocols. The simulations results are presented through performance lines that make possible constructing the conclusions about the behavior of the evaluated protocols.